The relationship between certain physical characteristics and body measurements in the performance of certain motor skills in karate among juniors aged 10-12 - Abed Elmalek; Ababsa, houssem (sports creativity, 2025)
Karate is a widely practiced sport throughout the world, encompassing both Kumite and Kata disciplines. Each discipline has its own specific physical attributes and body measurements that practitioners must possess if their goal is to reach the highest levels (although physical attributes and body measurements may be similar in some sports). A player's performance level is reflected in a set of components: physical attributes, body measurements, skill performance, psychological factors, physiological factors, and tactics. Regarding physical attributes, it has been said that "achievement in these disciplines is primarily related to speed and strength, in addition to other qualifications" (1). The importance of body measurements is also noted: "These measurements influence the development of muscular strength, speed, endurance, and flexibility, as well as the player's body's responsiveness to various surrounding conditions, physical efficiency, and the achievement of outstanding athletic results" (2). Kata is considered an exciting discipline, as the player faces challenges that they strive to overcome. Here, the player's physical attributes and body measurements come into play, facilitating their ability to overcome these challenges, in addition to other challenges inherent in the sport. Identifying the most important physical attributes and body measurements that positively influence a player's performance, and ranking them from most important to least important, will be crucial in selecting and training the most physically and mentally suitable players who can reach the highest levels. Knowing the most important physical attributes and body measurements of a karate player will greatly assist coaches in selecting suitable individuals in whom their efforts can bear fruit, thus saving time, effort, and money. This highlights the importance of the research, as karate is a complex sport that requires specific physical and physique characteristics for players to practice and achieve satisfactory results. Skillful performance is also a significant factor in success. Therefore, the researcher decided to study the most important physical attributes and body measurements of junior players aged 10-12 years. This research aims to help coaches assess the suitability of a player's attributes for reaching the highest levels. Physical attributes and body measurements are considered influential factors in skill performance in karate. Due to the limited information available on physical attributes and body measurements for this sport, and given the importance of skill performance and its significant impact on performance scores in this event,